2021
DOI: 10.3390/jcm10184078
|View full text |Cite
|
Sign up to set email alerts
|

Glycemic Variability Impacted by SGLT2 Inhibitors and GLP 1 Agonists in Patients with Diabetes Mellitus: A Systematic Review and Meta-Analysis

Abstract: To investigate the effect of sodium-glucose cotransporter 2 (SGLT-2) inhibitors and glucagon-like peptide 1 (GLP-1) agonists on glycemic variability (GV), the mean amplitude of glucose excursion (MAGE), mean blood glucose (MBG) levels, and percentage of time maintaining euglycemia were evaluated. Randomized controlled trials evaluating the efficacy of SGLT-2 inhibitors and GLP-1 agonists for treating people with diabetes were selected through searches of PubMed, EMBASE, and other databases. Sixteen studies wer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 17 publications
(10 citation statements)
references
References 43 publications
0
9
0
Order By: Relevance
“…This mechanism was confirmed by improved cardiovascular outcomes in acute coronary syndrome patients with strict glycemic control ( 41 , 42 ). A recent meta-analysis that included 16 studies showed that SGLT-2 inhibitors could effectively reduce the mean amplitude of glucose excursion and glycemic variability ( 43 ). Since AT1R/NADPH oxidase/SGLT1 and 2 pathways promote endothelial dysfunction, SGLT-2i provide a promising strategy to ameliorate endothelial function.…”
Section: Discussionmentioning
confidence: 99%
“…This mechanism was confirmed by improved cardiovascular outcomes in acute coronary syndrome patients with strict glycemic control ( 41 , 42 ). A recent meta-analysis that included 16 studies showed that SGLT-2 inhibitors could effectively reduce the mean amplitude of glucose excursion and glycemic variability ( 43 ). Since AT1R/NADPH oxidase/SGLT1 and 2 pathways promote endothelial dysfunction, SGLT-2i provide a promising strategy to ameliorate endothelial function.…”
Section: Discussionmentioning
confidence: 99%
“…Evidences suggested that brain insulin signaling regulates the homeostasis of peripheral energy metabolism through the autonomic nervous system and hypothalamic–pituitary axis ( 8 , 50 ). The incretins Glucagon-like peptide 1 (GLP-1) and glucose-dependent insulinotropic peptide (GIP), which were suggested to be efficacy in restoring insulin sensitivity ( 53 ), have shown potential in reducing GV in patients with Type 2 Diabetes ( 54 , 55 ). The neuroprotective effect of insulin administration has been reported in vivo ( 56 ) and in animal models ( 50 , 51 , 57 ) by alleviating glutamate excitotoxicity and reducing inflammatory response.…”
Section: Discussionmentioning
confidence: 99%
“… 10 Thus, MAGE may be able to better represent glucose fluctuation in this context. 7 , 11 Hence, in the current study, we used MAGE as a primary GV metric due to its extensibility.…”
Section: Introductionmentioning
confidence: 99%
“… 14 In addition, Heeyoung Lee et al compared and analyzed GLP-1 RAs and SGLT-2 inhibitors. 11 According to published studies, SGLT-2 inhibitors, GLP-1 RAs, and DPP-4 inhibitors show pharmacological differences in their mechanisms of action, but effectively reduce glucose levels, complications, and GV in diabetic patients. 11 , 14 However, in existing studies, it is difficult to ascertain the differences between individual drugs because direct comparison drugs for each drug pair exist in part.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation